BS EN IEC 60794-1-402. Optical Fibre Cables. Basic optical cable test procedures. Part 402. Lightning test method for optical aerial cables along electric power lines (OPGW, OPPC and OPAC), method H2 (14th February 2020) - British Standards Institution,
No abstract available